2014
DOI: 10.5194/acp-14-10465-2014
|View full text |Cite
|
Sign up to set email alerts
|

Model-simulated trend of surface carbon monoxide for the 2001–2010 decade

Abstract: Abstract. We present decadal trend estimates of surface carbon monoxide (CO) simulated using the atmospheric chemistry general circulation model ECHAM5/MESSy (EMAC; ECHAM5 and MESSy stand for fifth-generation European Centre Hamburg general circulation model and Modular Earth Submodel System, respectively) based on the emission scenarios Representative Concentration Pathways 4.29 %, respectively. We also find a reasonable correlation (R = 0.78) between the trends of EMAC surface CO and full 10-year monthly re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 118 publications
(135 reference statements)
3
30
1
Order By: Relevance
“…In agreement with numerous other studies (e.g. Dils et al, 2011;Worden et al, 2013;Petetin et al, 2016a), this decrease over Europe is mainly due to the reduction of CO anthropogenic emissions over the last decades (Yoon and Pozzer, 2014;Strode et al, 2016). The strongest decrease is observed at the traffic stations with best estimates of the trend ranging from -5.5 to -10% yr -1…”
Section: Trendssupporting
confidence: 78%
“…In agreement with numerous other studies (e.g. Dils et al, 2011;Worden et al, 2013;Petetin et al, 2016a), this decrease over Europe is mainly due to the reduction of CO anthropogenic emissions over the last decades (Yoon and Pozzer, 2014;Strode et al, 2016). The strongest decrease is observed at the traffic stations with best estimates of the trend ranging from -5.5 to -10% yr -1…”
Section: Trendssupporting
confidence: 78%
“…The main difference between the two CO-only simulations is the vertical distribution of the CO source from NMVOCs, which is three-dimensional in the improved simulation but only occurs in the surface layer in the base simulation. Yoon and Pozzer, 2014;Strode et al, 2016). The full GEOSChem benchmark is similarly conducted for a much more recent year (2013), and updating the benchmark dataset to include more recent airborne observations, including those in regions sensitive to biogenic emissions and chemical production, should be a priority for the GEOS-Chem community.…”
Section: Implications For Global Evaluation With Observationsmentioning
confidence: 99%
“…The negative AOD trend observed over eastern China is in line with the air quality regulations and the applied policies promoting the reduction in emissions over China. Van der A et al (2017) report on the decrease in aerosol precursor gases (SO 2 , NO 2 ) based on OMI, SCIAMACHY (Scanning Imaging Absorption Spectrometer for Atmospheric Cartography) and GOME-2 (Global Ozone Monitoring Experiment) satellite observations, while Yoon and Pozzer (2014) report on the decrease in biomass-burningrelated emissions. The decline in AOD over China is additionally observed by several authors (Kang et al, 2016;Zhang et al, 2017), with the suggested pivot point around 2011 (Zhao et al, 2017).…”
Section: Temporal Evolution Of Aod and D_aodmentioning
confidence: 99%